Carnivorous plants and their biotic interactions - Mithöfer, Axel (Journal of plant interactions, 2022)
Carnivorous plants reverse the order we expect in nature: here, animals do not feed on plants, but plants hunt and feed on animal prey, primarily insects, thereby enabling these plants to survive in nutrient-poor environments. In addition to this strategy, some carnivorous plants also form unique symbiotic relationships with animals other than insects to access nutrients. Other important interactions of carnivorous plants with insects, such as pollinators and herbivores, have received far less attention or have been largely neglected. This review describes and summarizes various ecologically relevant biotic interactions between carnivorous plants and other organisms reported in recent studies. In particular, our understanding on how carnivorous plants, for example, handle the pollinator-prey-conflict or interact with and respond to herbivores is still incomplete. Strategies and mechanisms on how carnivorous plants address these challenges are presented. Finally, future directions in carnivorous plant research are proposed.